Three new species of the genus Quedius (subgenus Microsaurus) from China (Coleoptera: Staphylinidae: Staphylinini: Quediina) - Cai, Yan-Peng; Zhao, Zong-Yi; Zhou, Hong-Zhang (Zootaxa, 2015)
Three new species of the subgenus Microsaurus Dejean, 1833 of the genus Quedius Stephens, 1829 are described based on specimens collected from China: Q. (Microsaurus) bilobus sp. nov. and Q. (Microsaurus) varius sp. nov. from Sichuan, and Q. (Microsaurus) cornutus sp. nov. from Yunnan. Line drawings and color illustrations of adults and genitalia of the new species are provided.